1998
DOI: 10.1056/nejm199811123392002
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Carotid Endarterectomy in Patients with Symptomatic Moderate or Severe Stenosis

Abstract: Endarterectomy in patients with symptomatic moderate carotid stenosis of 50 to 69 percent yielded only a moderate reduction in the risk of stroke. Decisions about treatment for patients in this category must take into account recognized risk factors, and exceptional surgical skill is obligatory if carotid endarterectomy is to be performed. Patients with stenosis of less than 50 percent did not benefit from surgery. Patients with severe stenosis (> or =70 percent) had a durable benefit from endarterectomy at ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,815
6
116

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,230 publications
(2,003 citation statements)
references
References 29 publications
28
1,815
6
116
Order By: Relevance
“…These results focus on the vessel lumen for purposes of comparison to x-ray angiography. The degrees of stenosis were divided into four categories, as commonly used (21). Three of the four patients in the Ͼ70% category subsequently received a carotid endarterectomy.…”
Section: Resultsmentioning
confidence: 99%
“…These results focus on the vessel lumen for purposes of comparison to x-ray angiography. The degrees of stenosis were divided into four categories, as commonly used (21). Three of the four patients in the Ͼ70% category subsequently received a carotid endarterectomy.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22] Outcome of these studies was a clinical cerebrovascular event, whether visible on computer tomography (CT) or not. As CMIs are too small to visualize on CT, they were not taken into account in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…[99][100][101][102][103][104][105][106] In patients with ischemia in the territory of a stenotic carotid artery, CEA within the first 2 weeks reduces the risk of stroke, 35,93 but the benefit of surgery diminishes with time after the initial event. 107 Transient monocular blindness (amaurosis fugax) is caused by temporary reduction of blood flow to an eye.…”
Section: Clinical Assessment Of Patients With Focal Cerebral Ischemicmentioning
confidence: 99%
“…37 Over 5 years, the rate of ipsilateral stroke, including perioperative events, was 15.7% with CEA compared with 22% for medically managed patients. 35,37,86,167 The ECST (European Carotid Surgery Trial), which was nearly concurrent with NASCET, randomized 2518 patients with stenosis using a different method of measurement whereby the minimal residual lumen through the zone of stenosis was compared with the ECVD Guideline: Executive Summary E93 estimated diameter of the carotid bulb rather than the distal internal carotid artery ( Figure 3). The study found a benefit of CEA for patients with 70% to 99% stenosis but no benefit in those with milder stenosis.…”
Section: Symptomatic Patientsmentioning
confidence: 99%